2020
DOI: 10.18494/sam.2020.2715
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Apple Taste Information Using Model Based on Hyperspectral Imaging and Electronic Tongue Data

Abstract: Taste is one of the most important criteria for evaluating the quality of apples. In this study, a correlation model using hyperspectral images and quantitative taste information was built for the nondestructive detection of apple taste information. Firstly, the images of 90 sets of Aksu apples were collected by a hyperspectral image system and quantitative values of taste information (sourness and sweetness) were measured using an SA-402B electronic tongue. Secondly, to overcome the difficulties in obtaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…At present, many scholars have made researches on identifying red jujube varieties based on HSI technology. Liu, He, et al (2020) and Liu, Liu, et al (2020) used CARS and other methods to select the characteristic wavelengths of red jujube samples. Although satisfactory results have been obtained, the number of characteristic wavelengths was large and the running time was long.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, many scholars have made researches on identifying red jujube varieties based on HSI technology. Liu, He, et al (2020) and Liu, Liu, et al (2020) used CARS and other methods to select the characteristic wavelengths of red jujube samples. Although satisfactory results have been obtained, the number of characteristic wavelengths was large and the running time was long.…”
Section: Discussionmentioning
confidence: 99%
“…CARS (Liu, He, et al, 2020; Liu, Liu, et al, 2020) is an effective variable selection method involving MC sampling coupled with partial least squares (PLS) model regression coefficients. The wavelengths with a large absolute weights of regression coefficients in the PLS model are reserved as new subsets through ARS each time, the wavelengths with lower weights are got rid of.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(24) It is based on the principle of structural risk minimization and has many advantages for pattern recognition problems, such as a small sample size, nonlinearity, and a high-dimensional feature space. (25) In the process of pattern recognition, the kernel function maps the feature vector to a space with a higher dimension and establishes a hyperplane in this space. Previous studies have shown that the Radial Basis Function (RBF) kernel function exhibits a good classification performance.…”
Section: Gwo-svmmentioning
confidence: 99%
“…Moreover, artificial intelligence and machine learning (ML) models can be used for prediction and modeling in the food industry [14]. With spectral images, HSI has been widely applied to evaluate the traits of meat products, including color, surface defects, damage, texture, water-holding capacity, flavor, freshness, and ripeness [4,[15][16][17][18][19][20][21]. Ma et al used HSI based on 400-1000 nm wavelengths to predict the different textural parameters of grass carp fillets during vacuum freeze-drying [4].…”
Section: Introductionmentioning
confidence: 99%